Degradation of sulfamethoxazole in bioelectrochemical system with power supplied by constructed wetland-coupled microbial fuel cells. (November 2017) - Zhang, Shuai; Yang, Xiao-Li; Li, Hua; Song, Hai-Liang; Wang, Ri-Cheng; Dai, Zhe-Qin
Graphical abstract: Highlights: Rapid removal of SMX in BER was simulated with a first-order kinetic model. Low current did not affect the degradation products but did promote SMX removal rate. Biotransformation was the main pathway of SMX elimination in BER. Stacked CW-MFCs supplied sufficient electricity to support BER for SMX degradation. Abstract: The removal rate and degradation pathway of Sulfamethoxazole (SMX) in bioelectrochemical system (BES) and the elimination dynamics of SMX in a BES driven by stacked constructed wetland-coupled microbial fuel cells (CW-MFCs) were investigated. The results found that SMX (30 mg L −1 ) was rapidly degraded in the BES, and the SMX removal kinetics was simulated well by a first-order kinetic model ( R 2 > 0.93). Low current had no effect on the degradation products but enhanced the SMX removal rate. Biotransformation was the main pathway for the SMX elimination in the BES. The CW-MFCs supplied adequate and stable electricity (0.84–1.01 V) to support the BES for rapid SMX degradation without additional energy inputs. The relative abundance of Methanosarcina (18.7%) and VadinCA11 (3.1%) increased with an increase in voltage up to 1.2 V. However, the opposite was observed for Methanosaeta and Methanomassiliicoccus . The current in the BES influenced the methanogenic communities.